2021
DOI: 10.21203/rs.3.rs-434597/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Short leukocyte telomeres predict 25-year Alzheimer’s disease incidence in non-APOE ε4-carriers

Abstract: Background: Leukocyte telomere length (LTL) has been shown to predict Alzheimer's disease (AD), albeit inconsistently. Failing to account for the competing risks between AD, other dementia types, and mortality, can be an explanation for the inconsistent findings in previous time-to-event analyses. Furthermore, previous studies indicate that the association between LTL and AD is non-linear and may differ depending on apolipoprotein E ( APOE ) ε4 allele carriage, the strongest genetic AD predictor. Methods: We a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 56 publications
0
3
2
Order By: Relevance
“…Contrary to our findings, Fani et al [36] reported a U-shaped relationship between TL and risk of AD, where both shorter and longer TL were associated with a higher AD risk. Significantly higher risk of AD with shorter leukocyte TL was also reported in non- APOE e4-carriers only in a prospective population cohort [37]. While previous MR studies reported a protective effect of genetically determined longer TL on AD risk [38,39], we did not find significant genetic associations with AD/ADRD or its subtypes in our MR analyses.…”
Section: Discussioncontrasting
confidence: 64%
See 1 more Smart Citation
“…Contrary to our findings, Fani et al [36] reported a U-shaped relationship between TL and risk of AD, where both shorter and longer TL were associated with a higher AD risk. Significantly higher risk of AD with shorter leukocyte TL was also reported in non- APOE e4-carriers only in a prospective population cohort [37]. While previous MR studies reported a protective effect of genetically determined longer TL on AD risk [38,39], we did not find significant genetic associations with AD/ADRD or its subtypes in our MR analyses.…”
Section: Discussioncontrasting
confidence: 64%
“…Significantly higher risk of AD with shorter leukocyte TL was also reported in non-APOE e4carriers only in a prospective population cohort [37]. While previous MR studies reported a protective effect of genetically determined longer TL on AD risk [38,39], we did not find significant genetic associations with AD/ADRD or its subtypes in our MR analyses.…”
Section: Discussioncontrasting
confidence: 60%
“…Longer TL also was associated with a lower risk of AD/ADRD across APOE genotypes (e3e3, e2, or e4). In contrast, a Sweden study (Hackenhaar et al, 2021) showed the association between short TL (first tertile) and a higher risk of AD in APOE non-e4 carriers only.…”
Section: Discussionmentioning
confidence: 77%
“…Relative leukocyte telomere length (RTL) was compared to the novel DNAm biomarkers, as an established blood-based biomarker previously associated with increased AD incidence in non-APOE ε4-carriers in our sample [63]. Peripheral blood leukocytes DNA was used to estimate normalized RTL as previously described [63,64], using a modi ed Cawthon's polymerase chain reaction method [65,66]. Preliminary visual inspection of our data indicated a potential differential RTL attrition between cases and controls.…”
Section: Covariatesmentioning
confidence: 99%